Facilitating the Professional Growth of Teachers in Networked Learning Communities (NLC) - Goh, Sao-Ee; Tan, Irene (Proceedings of the International Conference on Networked Learning, 2016)
Networked learning among teachers is a powerful form of professional learning as such learning informs and helps them understand their work, their influence, and their effects on themselves, their peers and their students (Lieberman & Wood, 2003). In Singapore, one of our key professional development programmes is engaging teachers in networked learning communities or NLCs. We define NLCs as networks of teachers across schools learning from one another, with one another, and on behalf of others. Networked learning is the process where individuals from different schools come together in a network to engage in purposeful and sustained developmental activities, informed by the public knowledge base, utilising their own know-how and co-constructing knowledge together (Jackson & Temperley, 2007). One of our greatest challenges in championing NLCs is facilitating and ensuring the growth of the teachers involved. While there are numerous studies which recognise the values and purpose of NLC (e.g., Cousin & Deepwell, 2005; Day, Hadfield, & Kellow, 2002; Jopling, 2006; Katz & Earl, 2007; Lieberman, 2000), as well as studies suggesting principles and features to foster successful NLCs (e.g., Jackson & Temperley, 2007; Katz & Earl, 2010), there is a surprising lack of literature on models that operationalise networked learning. Our solution is to develop a networked learning model that guides facilitators of networked learning communities in the learning and growth of their members. In developing this model, we are informed by existing literature as well as our own research on factors of successful NLCs. We call our research-informed model SPAR© which is short for Seeding, Planning, Applying, Reviewing, Celebrating. Embedded within the SPAR© model are several established protocols and tools to guide NLC facilitators in facilitating purposeful and deep networked learning. While the model is designed and intended for teachers and teacher-educators, we believe the underlying processes will also be relevant to other non-teacher related networked learning communities. We hope to share our research-informed model with participants at NLC 2016. Participant Outcomes Participants will: • understand the various principles of networked learning in the education context; • learn about a networked learning model developed and used by the Academy of Singapore Teachers in facilitating the growth of NLCs; • experience some tools and protocols embedded within the networked learning model; and • have meaningful conversations with professional learning leaders from the Academy of Singapore Teachers in facilitating NLCs.